Changes of Atmospheric Electric Potential Gradient at Poona during disturbed weather - SIVARAMAKRISHNAN, M. V. (MAUSAM, 1953)
A detailed study of the changes of atmospheric potential gradient during disturbed weather at Poona for 5 years 1936-40 has been made. From the analysis it is seen that if during rainfall the potential gradient is negative but without rapid variations the rainfall is associated with a quite atmosphere, whereas large and rapid changes in the potential gradient are usually associated with atmospheric disturbances having appreciable local ascending air currents Just as the rainfall occurring in showers. Changes in potential gradient are not closely associated with either the intensity or the variations of the rainfall. The field at the ground is not essentially different in thunderstorms from. that associated with showers. Two main types of potential gradient patterns have been recognised. (a) Wave Patterns (b) Symmetrical Patterns. Some of the patterns are seen to be associated with definite types of weather.